BODY COMPOSITION, FEEDING HABITS AND OFF-SCHOOL PHYSICS ACTIVITY PRACTICE. (Fiep Bulletin - online, 2013)
Poor communities culturally submitted to urban violence tend to induct children and adolescents to risky situations through lack of educational stimuli from the family, lack of motor stimuli, feeding rules and hygiene. It can be frequently perceived that physical inactivity and bad feeding habits lead to body composition alterations not only in adulthood and also to the development of a lot of chronic-degenerative diseases. This study has a direct and descriptive approach aiming to characterize feeding habits, off-school physical activity practice and body composition of students of a public school at a poor community. Data collection was carried through a questionnaire and anthropometric measures. It was verified a positive answer on motor stimuli and body composition and prevalence of obesity and overweight was not observed. As to feeding habits, a high consumption of sweeties, soft drinks and fat snacks was verified. Data suggest that educational and health promotion interventions on this community be based on strategies of development of good feeding habits.
Keywords: risky community; lack of food; children´s obesity